Digital Technology in the Field of Educational Services - Vinogradova, Marina V.; KulyaminÐ°, Ðžlga S.; Larionova, Anna A.; Maloletko, Alexandr N.; Kaurova, Olga V. (International Review of Management and Marketing, 2016)
The relevance of the investigated problem is conditioned by the rapid introduction of digital technologies into all practice areas, in particular, into the field of educational services The aim of the article is to present the results of the research on the trends of the digital technologies' usage in the field of educational services for the period 2005 -2015 y.y. The leading method for the study of this problem is represented by conduct a survey through questionnaires of the professors and students of Russian and foreign educational institutions for the period 2005 -2015 y.y., a sampling of more than 1000 people, that made it possible to objectify the results of the study. On the basis of the wide investigative material, the general regularities in the use of the digital technologies in education have been identified. As marked in the article, the role of the lecturer with the development of information technologies is changing into a new type of the lecturer - instructor for students. The very fact, that students actively use digital technologies, at the same time does not mean that they make use of them in order to increase the level of their training. The paper substantiates the fact that without the methodological working out of the introduction and use of digital technologies in the process of training, it will be difficult to monitor the changes. The article materials are of practical value to the participants of educational services field. The authors express their appreciation to the direction, professors and students of the educational institutions, participating in the survey. Key words: Digital Technologies, Education, Information, Educational Services JEL Classifications: A23, I23, I26